Does homeownership hinder labor market activity? Evidence from housing privatization and restitution in Brno - Stepan Mikula; Josef Montag (Masaryk University, Faculty of Economics and Administration, 2019)
We study the effects of homeownership on labor force participation and unemployment. We exploit housing privatization and restitution after the fall of communism as a source exogenous assignment of homeowner/renter status, using a unique dataset from the city of Brno, Czech Republic. We do not find any evidence of homeownership hindering labor force participation. In fact, our estimates suggest that homeownership reduces unemployment by four to six percentage points. Homeownership appears to decrease the risk of unemployment by about one third to one half, relative to renters. The estimated effects on labor force participation are systematically around zero.
Keywords: J21; J64; P14; P25; P26; R31; 330; homeownership; labor force participation; unemployment; housing privatization and restitution